Evaluating the Effects of Pharmacological Levels of Zinc Oxide, Diet Acidification and Dietary Crude Protein on Growth Performance of Nursery Pigs - W. M. Hutchens; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband; H. I. Calderón (Kansas Agricultural Experiment Station Research Reports, 2020)
A total of 360 weaned pigs (DNA 200 × 400; initially 12.9 lb BW) were used in a 42-d growth study to evaluate the effects of pharmacological levels of zinc oxide (ZnO), diet acidification, and dietary crude protein (CP) on pig performance. Pigs were weaned at approximately 21-d of age and were randomly assigned to pens (5 pigs per pen) and allotted to 1 of 8 dietary treatments with 9 pens per treatment. Experimental diets were fed from d 0 to 21 with a common diet fed from d 21 to 42. The eight treatment diets were arranged as a 2 × 2 × 2 factorial with main effects of Zn from ZnO (110 ppm from d 0 to 21 or 3,000 ppm from d 0 to 7, and 2,000 ppm from d 7 to 21), diet acidification, (without or with 1.2% sodium diformate), and dietary CP (21 or 18%, [1.40 vs. 1.20% standardized ileal digestible Lys, respectively]). Fecal samples were collected weekly to determine dry matter content. No 2- or 3-way interactions (P>0.05) were observed throughout the 42-d growth study for growth performance; however, there was a ZnO × acidifier × CP interaction (P<0.05) for fecal dry matter on d 7 and overall, where reducing CP without acidification increased fecal DM when ZnO was not in the diet, but had little effect when ZnO was present in the diet. From d 0 to 21, pigs fed added ZnO had improved (P<0.05) average daily gain (ADG), average daily feed intake (ADFI), feed efficiency (F/G), and increased d 21 body weight (BW) compared to those fed 110 ppm Zn. Added sodium diformate improved (P<0.05), ADG, F/G, and BW. Pigs fed 21% CP had improved (P<0.05) ADG and F/G and tended (P<0.10) to have increased d 21 BW. In the subsequent period (d 21 to 42) after the experimental diets were fed, there was no evidence of difference in growth performance among treatments. Overall (d 0 to 42), adding ZnO or sodium diformate from d 0 to 21 tended to increase ADG (P ≤ 0.10) with no evidence of difference in ADFI and F/G. Increasing dietary CP from 18 to 21% from d 0 to 21 improved (P<0.05) overall F/G. In summary, dietary addition of ZnO or sodium diformate independently improved nursery pig performance.
Keywords: zinc; acidification; crude protein; nursery pigs